Cosmopolitanism and Place - Stuhr, John J.; Medina, Jose M.; Wahman, Jessica, 1968- (Book collections on Project MUSE., 2017)
Addressing perspectives about who "we" are, the importance of place and home, and the many differences that still separate individuals, this volume reimagines cosmopolitanism in light of our differences, including the different places we all inhabit and the many places where we do not feel at home. Beginning with the two-part recognition that the world is a smaller place and that it is indeed many worlds, Cosmopolitanism and Place critically explores what it means to assert that all people are citizens of the world, everywhere in the world, as well as persons bounded by a universal and shared morality. -- Back cover